IET science, measurement & technology - Institution of Engineering and Technology (Institution of Engineering and Technology, 2007)
Publishes papers in science, engineering and technology underpinning electronic and electrical engineering, nanotechnology and medical instrumentation.
Keywords: Measurement : Periodicals; Electrical engineering : Periodicals; Electronics : Periodicals; Nanotechnology : Periodicals; Mesure : Périodiques; Génie électrique : Périodiques; Électronique : Périodiques; Electrical engineering; Electronics; Measurement; Nanotechnology; Engineering; Technology (General); Science (General)